Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbasis Quizizz untuk Meningkatkan Prestasi Belajar Peserta Didik di SMK Negeri 4 Gowa - Dewi Umrawati; Jamaluddin Jamaluddin; Ervi Novitasari (Institut Nalanda, 2024)
The research is a classroom action research aimed at improving the learning achievement of 10th grade students in agricultural tecnology and plant husbandry program at state vocational high school 4 Gowa. The independent variable in this study is the application of the teams games tournament cooperative leaening model based on quizizz, while the dependent variable is the learning achievement of students in the fundamentals of agribusiness plant subjects. The sample consists of the 10th grade class ATPH 1 SMK state 4 Gowa. Research data were obtained from learning outcome tests, including pre-tests & post-tests. Based on data analysis, data were obtained from learning outcome tests, with percentages in cycle 1 pre-test score 39,65% and post test score of 49,6%, and in cycle 2 a post test result of 85,88% was obtained. Based on data analysis, it can be concluded that the implementatiton of the cooperative learning model teams games tournament (TGT) based on quizizz, can improve the learning achievement of students in class X ATPH 1 at SMK Negeri 4 Gowa.